Efficacy and safety of chinese herbal foot bath for hypertension: A systematic review and meta-analysis - Tong Wu; Luolin Zhou; Xinru Liao; Yuewen He; Ronglin Xu; Daihong Luo (Elsevier, 2024)
Background: Hypertension is a prevalent condition with significant impacts on human health. Chinese herbal foot bath, a traditional Chinese medicine treatment, is believed to help manage hypertension. Objective: This systematic review aims to assess the efficacy of combining Chinese herbal foot bath with conventional treatment for hypertension. Methods: A thorough search across eight databases was conducted to identify relevant studies on Chinese herbal foot bath for hypertension. Randomized controlled trials examining the benefits and risks of using Chinese herbal foot bath combined with conventional treatment for hypertension were included. Blood pressure changes before and after the Chinese herbal foot bath were assessed, and outcomes were analyzed using Review Manager 5.3 software. The certainty of evidence was evaluated using the GRADE tool. Results: Compared to conventional treatment, Chinese herbal foot bath combined with conventional treatment demonstrated greater effectiveness in reducing systolic blood pressure (MD 6.69, 95% CI: 5.86 to 7.53, p < 0.00001) and diastolic blood pressure (MD 5.83, 95% CI: 5.23 to 6.43, p < 0.00001), which reported fewer adverse effects.These studies commonly present issues such as inadequate randomization, lack of blinding, and absence of independent testing for the purity or potency of herbs. Conclusion: The meta-analysis suggests that Chinese herbal foot bath combined with conventional treatment may effectively manage hypertension, with few adverse effects. However, high-quality clinical trials are still needed to confirm these findings due to methodological weaknesses in randomization, blinding, long-term follow-up, and independent testing for the purity and potency of herbs.